2020
DOI: 10.3904/kjim.2018.248
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of thymic stromal lymphopoietin and CRTH2 attenuates airway inflammation in a murine model of allergic asthma

Abstract: Background/Aims: Thymic stromal lymphopoietin (TSLP) is an epithelial cell-derived cytokine that plays a key role in Th2-mediated inflammation, both directly by promoting the proliferation of naïve CD4 Th2 cells, and indirectly by activating dendritic cells (DCs). TSLP-activated DCs induce the expansion of chemoattractant receptor homologous molecule expressed on Th2 (CRTH2) + CD4 + Th2 memory cells, which undergo a Th2 response and express prostaglandin D2 (PGD2) synthase. CRTH2, a PGD2 receptor, is a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Traditional mind–body exercises can improve the quality of life of COPD patients for three main reasons: (1) The most fundamental pathophysiological change in COPD is obstructive ventilatory impairment, making pulmonary function a crucial factor influencing patient quality of life. Through traditional mind–body exercises and respiratory regulation, patients increase thoracic and lung activity, expand chest volume, promote alveolar expansion, improve respiratory muscle fatigue, and enhance pulmonary function, thus alleviating respiratory difficulties and improving quality of life ( 50 , 51 ). (2) Long-term engagement in traditional mind–body exercises significantly improves tension, anxiety, anger, hostility, fatigue, and other emotions in patients ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional mind–body exercises can improve the quality of life of COPD patients for three main reasons: (1) The most fundamental pathophysiological change in COPD is obstructive ventilatory impairment, making pulmonary function a crucial factor influencing patient quality of life. Through traditional mind–body exercises and respiratory regulation, patients increase thoracic and lung activity, expand chest volume, promote alveolar expansion, improve respiratory muscle fatigue, and enhance pulmonary function, thus alleviating respiratory difficulties and improving quality of life ( 50 , 51 ). (2) Long-term engagement in traditional mind–body exercises significantly improves tension, anxiety, anger, hostility, fatigue, and other emotions in patients ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This scale tests COPD patients on items such as sputum, cough, sensations during stair climbing or uphill walking, chest tightness, confidence, household activities, energy, and sleep. It provides an assessment of patients' daily lives and physical and mental health, serving as an independent and comprehensive evaluation tool (49). Both the SGRQ and CAT scales are effective tools for assessing the health-related quality of life of stable COPD patients.…”
Section: Impact Of Traditional Mind-body Exercises On Quality Of Lifementioning
confidence: 99%
“…TSLP regulates the differentiation of CD4 + naive T lymphocytes to Th2 cells by inducing dendritic cells to produce IL-4, IL-5, IL-13, etc. Animal experiments have found that the specific expression of TSLP can induce AHR, airway inflammation, goblet cell hyperplasia, and lack of TSLP cannot produce allergen-induced lung inflammatory response 26 , 27 . It is suggested that TSLP is involved in airway inflammatory diseases, which is in accordance with Liu’s research 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of alarmins proved beneficial as an add-on therapy or in combination with other cytokine inhibitors. Blockade of TSLP together with CRTH2, a chemoattractant receptor homologue expressed on Th2 memory cells, attenuated eosinophilic inflammation and AHR in ovalbumin-challenged mice ( 43 ). In line with this, bispecific anti-TSLP, anti-IL-13 reagent was recently developed in a form of monovalent antibody called Zweimab, and bivalent bispecific antibody scaffold – Doppelmab ( 44 ).…”
Section: Alarmins As Targets For Asthma Therapymentioning
confidence: 99%